2001
DOI: 10.1590/s0102-311x2001000400037
|View full text |Cite
|
Sign up to set email alerts
|

Escolaridade materna: correlação com os indicadores obstétricos

Abstract: O objetivo deste estudo é estimar as associações entre a escolaridade materna, como variável dependente, e algumas variáveis constantes na Declaração de Nascido Vivo (DNV) do Ministério da Saúde. Em uma análise de 3.843 DNV da região de Guaratinguetá, São Paulo, relativas a partos hospitalares e nascimentos únicos, ocorridos no ano de 1998, foram encontradas associações estatisticamente significativas entre a menor escolaridade e ocorrência de baixo peso ao nascer; número de filhos vivos igual ou maior que trê… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
55

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 11 publications
2
24
0
55
Order By: Relevance
“…The variable schooling is not deemed valuable when completing the maternal death certificates in many studies. Several studies (18)(19) have shown risks to be proportionally inverse to the number of years of education. The illiteracy rate among black women is double the illiteracy rate among white women.…”
Section: Discussionmentioning
confidence: 99%
“…The variable schooling is not deemed valuable when completing the maternal death certificates in many studies. Several studies (18)(19) have shown risks to be proportionally inverse to the number of years of education. The illiteracy rate among black women is double the illiteracy rate among white women.…”
Section: Discussionmentioning
confidence: 99%
“…A escolaridade materna, no nosso estudo, não mostrou associação com a mortalidade em recém-nascidos de muito baixo peso, resultado diferente do referido por outros autores 3,6 , talvez por utilizarem amostras com recém-nascidos de maiores pesos ao nascimento e não em recém-nascidos de muito baixo peso. Estudos cujas amostras eram constituídas de recém-nascidos de muito baixo peso também não encontraram nenhuma associação.…”
Section: Discussionunclassified
“…Por apresentar dificuldades na coleta dessa informação, alguns autores mostraram que poderiam ser considerados outros fatores, como nível de escolaridade 3,6 ; estado conjugal materno 3,7,8 e local de moradia 5 .…”
Section: Introductionunclassified
“…24 The significant associations found in this study corroborate with other consulted studies. 7,10,11,13,[28][29][30] It was observed that the low maternal schooling is associated to negative outcomes for the maternal and child health, such as inadequate prenatal care with a low number of consultations and a high risk for low birth weight and prematurity. 28 The low coverage of prenatal care has been identified as a risk factor for the health of mothers and children 12 and has been associated to low birth weight and prematurity, 29 in this study, there was also a significant association to a low Apgar score at the 5 th minute.…”
Section: Factors Associated To Maternal and Child's Health In Rio Gramentioning
confidence: 99%